2015
DOI: 10.1017/s136898001500244x
|View full text |Cite
|
Sign up to set email alerts
|

Associations between cruciferous vegetable intake and selected biomarkers among women scheduled for breast biopsies

Abstract: Objective: To examine the relationship between dietary cruciferous vegetable intake and selected tumour biomarkers for histone acetylation (H3K9ac, H3K18ac, HDAC3 and HDAC6), proliferation (Ki-67) and cell-cycle regulation (p21) from breast tissue. Design: The study used baseline data of women recruited to participate in a clinical trial of sulforaphane supplement. Dietary cruciferous vegetable intake was collected through a validated Arizona Cruciferous Vegetable Intake Questionnaire. Breast tissue was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 23 publications
0
17
0
1
Order By: Relevance
“…Pro-apoptotic, anti-inflammatory and histone modulation are some of the known and crucial mechanisms by which SFN exerts chemoprevention. In addition to pre-clinical experiments, SFN has demonstrated promising results also in clinical studies in woman with breast ductal carcinoma in situ (DCIS) [ 72 ], glioblastoma cells [ 38 ] and prostate cancer [ 73 ]. Moreover, it was found that people who consumed cruciferous vegetables at least once a week have reduced risk of pharynx, oesophageal, colorectal, breast, oral cavity and kidney cancers [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pro-apoptotic, anti-inflammatory and histone modulation are some of the known and crucial mechanisms by which SFN exerts chemoprevention. In addition to pre-clinical experiments, SFN has demonstrated promising results also in clinical studies in woman with breast ductal carcinoma in situ (DCIS) [ 72 ], glioblastoma cells [ 38 ] and prostate cancer [ 73 ]. Moreover, it was found that people who consumed cruciferous vegetables at least once a week have reduced risk of pharynx, oesophageal, colorectal, breast, oral cavity and kidney cancers [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a double-blinded, randomized, placebo-controlled clinical trial, 78 senior patients with increasing PSA levels after radical prostatectomy were given 60 mg sulforaphane 3 times daily for 6 months, a much lower plasma PSA level were found in the sulforaphane treated group, which potentially suggests a promising treatment in recurrence of prostate cancer after prostatectomy (42). A randomized controlled clinical study consisting of 54 women subjects revealed a mean 81.7 g/d intake of cruciferous vegetable, enriching of SFN, for over 4 years (August 2009 to December 2013) was associated with a lower level of Ki-67, a cellular marker for proliferation, in breast ductal carcinoma in situ tissue, which strengthen the correlation of cruciferous vegetable consumption and lowering breast cancer risk (43). …”
Section: The Importance Of Dose In the In Vitro And In Vivo Chemoprevmentioning
confidence: 84%
“…A few small clinical trials have been conducted to determine whether consumption of broccoli sprout extracts shows efficacy against breast cancer biomarkers in women without invasive breast cancer who were scheduled for breast biopsies after a mammogram with intriguing results on epigenetic effects that require further investigation with larger and more comprehensive trials. In subjects with a history of breast cancer, intake of ≥14 cups per week of cruciferous vegetables for 3 weeks was seen to significantly reduce urinary 8‐hydroxy‐2′‐deoxyguanosine, a marker of oxidative stress, likely indicating the utility of cruciferous vegetables in cancer patient nutrition.…”
Section: Clinical Trials With Disease‐related Outcomes Using Isothiomentioning
confidence: 99%